FACTORS INFLUENCING STUDENT PERCEPTIONS OF TAX EVASION - Puspanita, Intan; Machfuzhoh, Asih (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2024)
This study aims to examine the factors that influence students' perceptions of ethical tax evasion actions. The population of this study were students majoring in accounting and tax administration at the Faculty of Economics and Business, Universitas Sultan Ageng Tirtayasa. Sampling was carried out based on purposive sampling with the type of judgment. The stages in this study were carried out by collecting data through questionnaires distributed to accounting and tax administration students who had taken taxation courses and continued with data analysis. The data of this study are primary data and were analyzed using validity tests, reliability tests, normality tests, multicollinearity tests, heteroscedasticity tests and multiple linear regression analysis tests. The results of this study indicate that the taxation system and money ethic have a positive and significant effect on the ethical perception of tax evasion. While the variables of fairness and tax sanctions have a negative effect on the ethical perception of tax evasion. The results of this study also show that the four variables together can influence the ethical perception of tax evasion actions.